2013
DOI: 10.1371/journal.pone.0066242
|View full text |Cite
|
Sign up to set email alerts
|

Pentose Phosphate Pathway Function Affects Tolerance to the G-Quadruplex Binder TMPyP4

Abstract: G-quadruplexes form in guanine-rich regions of DNA and the presence of these structures at telomeres prevents the activity of telomerase in vitro. Ligands such as the cationic porphyrin TMPyP4 stabilise G-quadruplexes and are therefore under investigation for their potential use as anti-cancer drugs. In order to investigate the mechanism of action of TMPyP4 in vivo, we carried out a genome-wide screen in the budding yeast Saccharomyces cerevisiae. We found that deletion of key pentose phosphate pathway (PPP) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…DIXY is an online data visualization tool for browsing QFA fitness plots, which show evidence for genetic interaction by comparing fitnesses of strains in a query screen with fitnesses in a control screen ( Addinall et al 2011 ). QFA screen data presented in this paper along with data from ( Andrew et al 2013 ) can be visualized here: http://bsu-srv.ncl.ac.uk/dixy-pol/viz/ . Note that the DAmP alleles are missing from the data obtained in Andrew et al (2013) .…”
Section: Methodsmentioning
confidence: 99%
“…DIXY is an online data visualization tool for browsing QFA fitness plots, which show evidence for genetic interaction by comparing fitnesses of strains in a query screen with fitnesses in a control screen ( Addinall et al 2011 ). QFA screen data presented in this paper along with data from ( Andrew et al 2013 ) can be visualized here: http://bsu-srv.ncl.ac.uk/dixy-pol/viz/ . Note that the DAmP alleles are missing from the data obtained in Andrew et al (2013) .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, TMPyP4 can also interact with some G-rich sequences and stabilize i-motif structures that promote the formation of G-quadruplexes [89, 90. TMPyP4 is thus a promising agent as a lead compound for a novel anti-cancer therapy targeting G-quadruplexes 91 . Owing to the poor selectivity of TMPyP4, however, TMPyP4 itself cannot be used as a therapeutic.…”
Section: C-myc As a Therapeutic Targetmentioning
confidence: 99%
“…Previous studies have shown that TMPyP4 can induce calcium release by direct interaction with the Ca2+ release protein from sarcoplasmic reticulum [51]. Furthermore, studies in yeast suggest that TMPyP4 can induce a cellular oxidative stress response that could affect calcium homeostasis [52]. TMPyP4 rescue of calcium homeostasis in premutation fibroblasts could theoretically involve similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%